2019
DOI: 10.1080/02713683.2019.1659976
|View full text |Cite
|
Sign up to set email alerts
|

Intrasession Repeatability of Biometric Measurements Obtained with a Low-Coherence Interferometry System in Pseudophakic Eyes

Abstract: Purpose: To evaluate the intrasession repeatability of the biometric measurements obtained with a low coherence reflectometry optical biometer in pseudophakic eyes implanted with two different types of intraocular lens (IOL). Methods: Prospective, single-center, comparative study including 69 eyes of 69 patients with ages ranging from 51 to 92 years. Previous uncomplicated cataract surgery had been performed in all patients 1 to 2 months before measurements, with implantation of the Acrysof SN60WF IOL in 35 ey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“… 9 Ruiz-Belda et al evaluated 53 healthy eyes and recorded a mean S w of 0.26 and 0.24 D for K1 and K2, respectively; recently, Fukumitsu et al, for 69 cataract eyes, reported S w values of 0.03 to 0.05 mm and 0.03 to 0.09 for AL and ACD, respectively. 10 , 11 …”
Section: Discussionmentioning
confidence: 99%
“… 9 Ruiz-Belda et al evaluated 53 healthy eyes and recorded a mean S w of 0.26 and 0.24 D for K1 and K2, respectively; recently, Fukumitsu et al, for 69 cataract eyes, reported S w values of 0.03 to 0.05 mm and 0.03 to 0.09 for AL and ACD, respectively. 10 , 11 …”
Section: Discussionmentioning
confidence: 99%
“…In the current study, a low-coherence interferometry biometer was used to measure the ACD postoperatively, which has been shown to provide consistent measurements of ACD and axial length in pseudophakic eyes [21]. The ACD measurement was used to determine the IOL real position, which is not ELP, as previously mentioned.…”
Section: Discussionmentioning
confidence: 86%
“…Visual acuity, subjective and objective refraction, anterior and posterior segment findings on slit lamp examination, and pseudophakic biometric data were obtained in all patients at 1 and 6 months after surgery. Only pseudophakic AXL and ACD measurements were collected during the follow-up considering that they have been to be consistent enough for research purposes [21]. It should be considered that an extremely poor consistency of the pseudophakic lens thickness measurements provided by the biometry device used in the current study was previously documented [21].…”
Section: Ocular Examination and Follow-upmentioning
confidence: 98%
See 2 more Smart Citations